Dermatology in Clinical Practice - Lanigan, S.W.; Zaidi, Zohra; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2010)
Skin problems are common complaints, as many as one in five of all primary care consultations are for dermatologic reasons, yet many clinicians find skin rashes difficult to diagnose. Dermatology in Clinical Practice has been created to assist all physicians, but particularly for primary care physicians, helping them in developing a methodical approach to manage patients with dermatologic symptoms. The authors focus on the common skin problems, and discuss the diagnosis and treatment of these disorders in depth. The book also details topical, systemic and the physical modalities used in treating skin disease, while The urare skin diseases are only mentioned when required. Cutaneous manifestations of systemic diseases are reviewed, enabling readers to correlate common medical and dermatologic findings. The primary care physician often refers cases to dermatology clinics for more complex dermatologic procedures, such as phototherapy, cryosurgery, and laser surgery. These procedures and a review of the diagnostic process leading up to their use are included in a carefully structured appendix. This book is a vital practical reference for primary care, family medicine, and emergency medicine physicians, in addition to nursing staff and other support staff involved in the management of patients presenting with dermatologic conditions.
Skin: Structure and Function -- Immune System of the Skin -- Diagnosis of Skin Disease -- Bacterial Infections -- Superficial Fungal Infections -- Viral Infections -- Parasitic Infestations and Diseases Caused by Arthropods -- Eczema -- Keratinizing and Papulosquamous Disorders -- Diseases of Connective Tissue -- Bullous Disorders: Autoimmune and Childhood Bullous Dermatoses -- Vasculitis, Common Erythemas, and Lymphatic Disorders -- Exanthems and Hypersensitivity Syndromes -- Urticaria -- Pruritus -- Leg Ulcers -- Disorders of Pigmentation -- Disorders of Ultraviolet Radiation and Injuries Due to Cold -- Diseases of the Sebaceous, Sweat, and Apocrine Glands -- Hair Disorders -- Nail Disorders -- Diseases of the Subcutaneous Tissue -- Tumors of the Skin -- Naevi and Hereditary Disorders of the Skin -- Skin and Malnutrition -- Skin and Systemic Disease -- Skin and the Psyche -- Erythroderma -- Ages of Man and Their Dermatoses -- Diseases of the Oral Cavity -- Diseases of the External Genitalia -- Miscellaneous Disorders -- Drug Reactions -- Management of Skin Diseases.
Keywords: Medicine; Dermatology; Family medicine; Medicine & Public Health; Dermatology; General Practice / Family Medicine